PENERAPAN MODEL PBL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI GERAK LURUS DI SMP - Fitriah, Fitriah; Djudin, Tomo; Mahmudah, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the application of the Problem Based Learning (PBL) model in improving studentsâ€™ critical thinking skills in straight motion in SMP Negeri 10 Pontianak. The research method used was an experimental research method in the form of pre-experimental design with one group pretest-posttest design model. The sampling technique used in this study was intact group technique and obtained class VIII A with a total of 35 students. The ability of critical thinking was seen from the explanation aspect in this research. The instrument of this research have5 description test. Based on the results of Wilcoxon test obtained a significant increase in critical thinking abilities with asymp.sig (2-tailed) below 0,05 (0,000<0,05). The results of this study were supposed to be applied by the teacher as an alternative to improve studentsâ€™ critical thinking skills.Â Keywords: Critical thinking skill, explanation aspect, problem based learning, straight motion